Primary versus postoperative stereotactic radiosurgery for acromegaly: a multicenter matched cohort study - Mohammed, Nasser; Ding, Dale; Hung, Yi-Chieh; Xu, Zhiyuan; Lee, Cheng-Chia; Kano, Hideyuki; Martínez-Álvarez, Roberto; Martínez-Moreno, Nuria; Mathieu, David; Kosak, Mikulas; Cifarelli, Christopher P; Katsevman, Gennadiy A; et al. (Journal of neurosurgery, 2020)
OBJECTIVE: The role of primary stereotactic radiosurgery (SRS) in patients with medically refractory acromegaly who are not operative candidates or who refuse resection is poorly understood. The aim of this multicenter, matched cohort study was to compare the outcomes of primary versus postoperative SRS for acromegaly. METHODS: The authors reviewed an International Radiosurgery Research Foundation database of 398 patients with acromegaly who underwent SRS and categorized them into primary or postoperative cohorts. Patients in the primary SRS cohort were matched, in a 1:2 ratio, to those in the postoperative SRS cohort, and the outcomes of the 2 matched cohorts were compared. RESULTS: The study cohort comprised 78 patients (median follow-up 66.4 months), including 26 and 52 in the matched primary and postoperative SRS cohorts, respectively. In the primary SRS cohort, the actuarial endocrine remission rates at 2 and 5 years were 20% and 42%, respectively. The Cox proportional hazards model showed that a lower pre-SRS insulin-like growth factor-1 level was predictive of initial endocrine remission (p = 0.03), whereas a lower SRS margin dose was predictive of biochemical recurrence after initial remission (p = 0.01). There were no differences in the rates of radiological tumor control (p = 0.34), initial endocrine remission (p = 0.23), biochemical recurrence after initial remission (p = 0.33), recurrence-free survival (p = 0.32), or hypopituitarism (p = 0.67) between the 2 matched cohorts. CONCLUSIONS: Primary SRS has a reasonable benefit-to-risk profile for patients with acromegaly in whom resection is not possible, and it has similar outcomes to endocrinologically comparable patients who undergo postoperative SRS. SRS with medical therapy in the latent period can be used as an alternative to surgery in selected patients who cannot or do not wish to undergo resection.
Keywords: acromegaly; growth hormone; primary radiosurgery; Gamma Knife; pituitary adenoma; stereotactic radiosurgery; pituitary surgery